Optimisation of spray forming ni superalloys via process modelling and on-line monitoring - Mi, J; Grant, P (2007)
The optimisation of spray forming IN718 alloy rings for aeroengine applications was investigated using both modelling and experimental approaches. A multiphysics numerical model has been developed and implemented to assist in the optimisation of the spray forming process.IN718 alloy ring preforms were spray formed at University of Oxford (UK) and The University of Bremen (Germany). A variety of on-line monitoring facilities were integrated onto spray forming units to (1) investigate the dynamics of alloy melt atomisation and droplet deposition at a sprayed surface; and (2) acquire ring preform thermal history and various thermal boundary conditions for the numerical model. Modelling and experiments were performed iteratively to investigate the effects of key spray forming parameters including gas metal flow ratio, atomiser scan, substrate heating schemes on the resulting ring preform shape, internal heat flow and solidification. It was found that preform top surface temperature and alloy liquid fraction inside the preform during spray forming were critical factors in governing the formation of macro/microporosity and the grain size of as-sprayed preforms. In the optimised conditions, IN718 alloy ring preforms were characterised by a microporosity of less than 1.5% and randomly oriented equaxied grains of 20-50 mu m.